Modelling urban water management transitions: A case of rainwater harvesting. (July 2018) - Castonguay, Adam C.; Urich, Christian; Iftekhar, Md Sayed; Deletic, Ana
Abstract: A promising way to address the growing demand for water supply and improve the liveability of cities is to invest in decentralised multifunctional urban water technologies. However, the adoption of multifunctional water technologies is a complex issue that requires cross-disciplinary approaches. This paper uses an agent-based model that integrates economic and environmental factors to explore and simulate the decision-making and interactions of two types of agents: a regulator and households. The model is applied to evaluate strategies to increase the adoption of rainwater tanks in a suburb of Melbourne, a city that has often suffered from severe droughts. The model was able to replicate the uptake of rainwater tanks by households for 2005–2014, the period known as the 'Millennium Drought'. Results indicate that using economic instruments alone may have been insufficient to promote the adoption of rainwater tanks, and that water restrictions have had a major impact on the uptake. Highlights: Development of a model that simulates the adoption of urban water technologies was presented. The model was successfully validated for a case of rainwater harvesting in a suburb of Melbourne, Australia. It was found that water restrictions have had a major impact on the adoption of rainwater tank. Rainwater tank adoption could only be enabled by a combination of factors.